2021
DOI: 10.1029/2021gl095839
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Photoelectron Energy Spectra Derived From Coincident FUV and Radio Measurements

Abstract: We present a method for estimating incident photoelectrons' energy spectra as a function of altitude by combining global scale far‐ultraviolet (FUV) and radio‐occultation (RO) measurements. This characterization provides timely insights important for accurate interpretation of ionospheric parameters inferred from the recently launched Ionospheric Connection Explorer (ICON) observations. Quantification of photoelectron impact is enabled by the fact that conjugate photoelectrons (CPEs) directly affect FUV airglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…At high altitudes (above ∼300 km), where the mean free path of photoelectrons is greater than the atmospheric scale height, photoelectrons can escape from the local ionosphere and travel to the opposite hemisphere along geomagnetic field lines (Hanson, 1963; Nagy & Banks, 1970; Richards & Peterson, 2008; Schunk & Nagy, 1978; Urco et al., 2021). The photoelectrons from the sunlit conjugate hemisphere result in ionization and heating of the neutrals and electrons in the dark hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…At high altitudes (above ∼300 km), where the mean free path of photoelectrons is greater than the atmospheric scale height, photoelectrons can escape from the local ionosphere and travel to the opposite hemisphere along geomagnetic field lines (Hanson, 1963; Nagy & Banks, 1970; Richards & Peterson, 2008; Schunk & Nagy, 1978; Urco et al., 2021). The photoelectrons from the sunlit conjugate hemisphere result in ionization and heating of the neutrals and electrons in the dark hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…By combining global scale far-UV measurements by ICON and radio-occultation measurements from COSMIC2 a method was developed to estimate the incident photoelectron’s energy spectra as a function of altitude (Urco et al. 2021 ). Quantification of photoelectron impact is enabled by the fact that CPEs directly affect FUV airglow emissions but not radio occultation measurements.…”
Section: Science Resultsmentioning
confidence: 99%
“… 2012 ), while a latter study (Urco et al. 2021 ) identified an up to 20-30% 135.6-nm radiance contribution to nighttime recombination emissions, enabling the identification and removal of these emissions, which are surprisingly abundant in nighttime observations, prior to retrieval of O + density profiles. This latter FUV study included GOLD observations as well, finding an initial offset bias multiplier of 0.5 between simultaneous GOLD and ICON measurements, with the ICON intensities being lower than GOLD.…”
Section: Scientific Findingsmentioning
confidence: 99%
“… 2021 ), where a second paper investigated the FUV emission-producing effects of early morning photoelectron fluxes flowing downward along magnetic field lines from magnetically-conjugate sunlit regions (Urco et al. 2021 ). This study suggested a list of corrections to the photoelectron component of the SAMI2-PE ionospheric model (Varney et al.…”
Section: Scientific Findingsmentioning
confidence: 99%
See 1 more Smart Citation